2009
DOI: 10.2337/db09-0635
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolic Alterations in Rats With Diabetic Ketoacidosis

Abstract: OBJECTIVECerebral edema is a life-threatening complication of diabetic ketoacidosis (DKA) in children. Recent data suggest that cerebral hypoperfusion and activation of cerebral ion transporters may be involved, but data describing cerebral metabolic alterations during DKA are lacking.RESEARCH DESIGN AND METHODSWe evaluated 50 juvenile rats with DKA and 21 normal control rats using proton and phosphorus magnetic resonance spectroscopy (MRS). MRS measured cerebral intracellular pH and ratios of metabolites incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
6
34
0
Order By: Relevance
“…23,24 Brain lactate levels are elevated and levels of high-energy phosphates are decreased. 25 These findings are similar to those observed during cerebral hypoxia or ischemia. [26][27][28][29] During DKA treatment with insulin and saline, CBF is elevated, and vasogenic edema develops.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…23,24 Brain lactate levels are elevated and levels of high-energy phosphates are decreased. 25 These findings are similar to those observed during cerebral hypoxia or ischemia. [26][27][28][29] During DKA treatment with insulin and saline, CBF is elevated, and vasogenic edema develops.…”
Section: Discussionsupporting
confidence: 84%
“…Brain levels of high-energy phosphates and ratios of N-acetylaspartate to creatine (an indicator of neuronal health) decline during initial treatment with insulin and saline. 25 These changes are similar to those observed during reperfusion after a hypoxic/ischemic insult. 6 to -0.6), P = .80.…”
Section: Discussionsupporting
confidence: 77%
“…56,84 Brain lactate levels are elevated and levels of high-energy phosphates are decreased. 85 However, after resuscitation has commenced, cerebral blood flow and ADC increase and high-energy phosphates and ratios of N-acetylaspartate to creatinine (an indicator of neuronal health) decline in a similar fashion to that which occurs during the phases of cerebral injury from hypoxia-ischemia. 85 These MR changes do not seem to correlate with speed of rehydration during resuscitation.…”
Section: Hyperglycemia and Ketoacidosismentioning
confidence: 94%
“…BBB dysfunction may be secondary to DKA-associated inflammation and leukocyte adherence to the brain microvascular endothelium (16,45). DKA-induced BBB permeability may exacerbate increases in brain glucose, lactate, and ketone levels during DKA (13,28,55) and underlie the vasogenic edema observed on brain MRI with apparent diffusion coefficients (19, 23, 29). In this study, we examined the potential for cellular DKA-CE to be mediated by changes in CSF composition during DKA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One study on a mixed population of adults and adolescents demonstrated that DKA CSF had increased glucose, ketones, lactate, and osmolality, whereas the bicarbonate was reduced (44); during DKA treatment, all values approached normal values. Noninvasive NMR and MRS imaging have also demonstrated altered CSF composition during DKA, which included elevated glucose, lactate, and ketones, and reduced intracerebral pH (8,13,28,55). Thus, experimental aCSF was approximated to these studies.…”
Section: Methodsmentioning
confidence: 99%